Does meter-scale snow data matter for modeling alpine plant distribution? A comparison of four data sources at two resolutions - Andreas Kollert; Kryštof Chytrý; Norbert Helm; Karl Hülber; Dietmar Moser; Johannes Wessely; Stef Lhermitte; Simon Gascoin; Andreas Mayr; Patrick Saccone; Johannes Hausharter; Michael Warscher; et al. (Ecological Modelling, 2026)

Background concentrations of airborne, culturable fungi and dust particles in urban, rural and mountain regions - Doris Haas; Mihaela Ilieva; Theresa Fritz; Herbert Galler; Juliana Habib; Angela Kriso; Michael Kropsch; Petra Ofner-Kopeinig; Franz F. Reinthaler; Andreas Strasser; Eduard Zentner; Michael Schalli (Science of The Total Environment, 2023)

Pseudomonas syringae DC3000 infection increases glucosylated N-glycans in Arabidopsis thaliana - Gernot Beihammer; Andrea Romero-Pérez; Daniel Maresch; Rudolf Figl; Réka Mócsai; Clemens Grünwald-Gruber; Friedrich Altmann; Els J. M. Van Damme; Richard Strasser (Glycoconjugate Journal, 2023)
Studying the interaction between the hemibiotrophic bacterium Pseudomonas syringae pv. tomato DC3000 and Arabidopsis thaliana has shed light onto the various forms of mechanisms plants use to defend themselves against pathogen attack. While a lot of emphasis has been put on investigating changes in protein expression in infected plants, only little information is available on the effect infection plays on the plants N-glycan composition. To close this gap in knowledge, total N-glycans were enriched from P. syringae DC3000-infected and mock treated Arabidopsis seedlings and analyzed via MALDI-TOF–MS. Additionally, fluorescently labelled N-glycans were quantified via HPLC-FLD. N-glycans from infected plants were overall less processed and displayed increased amounts of oligomannosidic N-glycans. As multiple peaks for certain oligomannosidic glycoforms were detected upon separation via liquid chromatography, a porous graphitic carbon (PGC)-analysis was conducted to separate individual N-glycan isomers. Indeed, multiple different N-glycan isomers with masses of two N-acetylhexosamine residues plus 8, 9 or 10 hexoses were detected in the infected plants which were absent in the mock controls. Treatment with jack bean α-mannosidase resulted in incomplete removal of hexoses from these N-glycans, indicating the presence of glucose residues. This hints at the accumulation of misfolded glycoproteins in the infected plants, likely because of endoplasmic reticulum (ER) stress. In addition, poly-hexose structures susceptible to α-amylase treatment were found in the DC3000-infected plants, indicating alterations in starch metabolism due to the infection process.

BCL-2 protein family: attractive targets for cancer therapy - Deeksha Kaloni; Sarah T Diepstraten; Andreas Strasser; Gemma L Kelly (Apoptosis, 2023)
Acquired resistance to cell death is a hallmark of cancer. The BCL-2 protein family members play important roles in controlling apoptotic cell death. Abnormal over-expression of pro-survival BCL-2 family members or abnormal reduction of pro-apoptotic BCL-2 family proteins, both resulting in the inhibition of apoptosis, are frequently detected in diverse malignancies. The critical role of the pro-survival and pro-apoptotic BCL-2 family proteins in the regulation of apoptosis makes them attractive targets for the development of agents for the treatment of cancer. This review describes the roles of the various pro-survival and pro-apoptotic members of the BCL-2 protein family in normal development and organismal function and how defects in the control of apoptosis promote the development and therapy resistance of cancer. Finally, we discuss the development of inhibitors of pro-survival BCL-2 proteins, termed BH3-mimetic drugs, as novel agents for cancer therapy.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Competitive association binding kinetic assays: a new tool to detect two different binding orientations of a ligand to its target protein under distinct conditions? - Hans-Joachim Wittmann; Andrea Strasser (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Modeling the Effect of the Selective S1P1 Receptor Modulator Ponesimod on Subsets of Blood Lymphocytes - Dominik Lott; Andreas Krause; Christian A. Seemayer; Daniel S. Strasser; Jasper Dingemanse; Thorsten Lehr (Pharmaceutical Research, 2017)

Modulation of GPCRs by monovalent cations and anions - Andrea Strasser; Hans-Joachim Wittmann; Erich H. Schneider; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Mathematical analysis of the sodium sensitivity of the human histamine H3 receptor - Hans-Joachim Wittmann; Roland Seifert; Andrea Strasser (In Silico Pharmacology, 2014)
Purpose It was shown by several experimental studies that some G protein coupled receptors (GPCR) are sensitive to sodium ions. Furthermore, mutagenesis studies or the determination of crystal structures of the adenosine A 2A or δ-opioid receptor revealed an allosteric Na + binding pocket near to the highly conserved Asp 2.50 . Within a previous study, the influence of NaCl concentration onto the steady-state GTPase activity at the human histamine H 3 receptor (hH 3 R) in presence of the endogenous histamine or the inverse agonist thioperamide was analyzed. The purpose of the present study was to examine and quantify the Na + -sensitivity of hH 3 R on a molecular level. Methods To achieve this, we developed a set of equations, describing constitutive activity and the different ligand-receptor equilibria in absence or presence of sodium ions. Furthermore, in order to gain a better understanding of the ligand- and Na + -binding to hH 3 R on molecular level, we performed molecular dynamic (MD) simulations. Results The analysis of the previously determined experimental steady-state GTPase data with the set of equations presented within this study, reveals that thioperamide binds into the orthosteric binding pocket of the hH 3 R in absence or presence of a Na + in its allosteric binding site. However, the data suggest that thioperamide binds preferentially into the hH 3 R in absence of a sodium ion in its allosteric site. These experimental results were supported by MD simulations of thioperamide in the binding pocket of the inactive hH 3 R. Furthermore, the MD simulations revealed two different binding modes for thioperamide in presence or absence of a Na + in its allosteric site. Conclusion The mathematical model presented within this study describes the experimental data regarding the Na + -sensitivity of hH 3 R in an excellent manner. Although the present study is focused onto the Na + -sensitivity of the hH 3 R, the resulting equations, describing Na + - and ligand-binding to a GPCR, can be used for all other ion-sensitive GPCRs.

Pharmacological profile of astemizole-derived compounds at the histamine H1 and H4 receptor—H1/H4 receptor selectivity - Eva Wagner; Hans-Joachim Wittmann; Sigurd Elz; Andrea Strasser (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Messung molekularer Interaktion mit dynamischen Oberflächensensoren - Ralf Strasser; Dirk Scholl; Paul Hampel; Andreas Langer; Ulrich Rant (BIOspektrum, 2012)

Role of the second and third extracellular loops of the histamine H4 receptor in receptor activation - Irena Brunskole; Andrea Strasser; Roland Seifert; Armin Buschauer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

The pro-apoptotic BH3-only protein Bid is dispensable for development of insulitis and diabetes in the non-obese diabetic mouse - Zia U. A. Mollah; Jibran Wali; Mark D. McKenzie; Balasubramanian Krishnamurthy; Kate L. Graham; Stacey Fynch; Joshua Szanyi; Pere Santamaria; Thomas Brodnicki; Janette Allison; Andreas Strasser; Thomas W. H. Kay; et al. (Apoptosis, 2011)

The molecular control of DNA damage-induced cell death - Leigh Coultas; Andreas Strasser (Apoptosis, 2000)